Exploring the Impact of Social Determinants of Health on Post-covid Behavior - Niciza, Jonathan; Iqbal, Faiza; Inuwa, Ahmadu; Uche Edwin, Cynthia; George, Prince (Journal of Indian Academy of Forensic Medicine, 2023)
Problem: The COVID 19 pandemic has had a very strong and negative impact in several sectors of society, the economy and health on post-COVID behavior. Although it has caused a very large and generalized socio-economic and health crisis with regard to the labor market, employment and health, this pandemic has above all contributed to the increase in health inequalities, the loss of jobs due to the breakdown of resources in families, anxiety and depression, not to mention the loss of social ties and capital due to prolonged isolation; all of these are confirmed as social determinants of health.Objectives: Describe the social determinants of health that impact post-COVID behavior, determine the impact of social determinants of health on post-COVID behavior, analyze the consequences of the social determinants of health that impact post-COVID behavior and propose effective solutions to combat the social determinants of health on post-COVID behavior.Method: Qualitative and quantitative methods were used and it is the qualitative data coding system that allowed us to achieve reliable results. Using Alain Bouchard's sampling technique, 78 health professionals were selected. Quantitative data were analyzed using statistical software for the social sciences.Results : This article has highlighted the direct or indirect impact of the social determinants of health that impact post-COVID behavior such as barrier measures put in place by the WHO and the particularities of the virus on the behavior of the population. such as the determinants of health that have stimulated the individual to have good sanitary behavior, namely washing their hands often, which is a positive act for the good health of the population, the members of the community are made aware of going to the health facilities for early detection, community engagement in health prevention is the result of determinants of health and social well-being.Outlook: After the onset of COVID-19, we have observed an enhancement in hygiene protocols and the implementation of hygiene procedures, social distancing, and the provision of personal protective gear. Additionally, there has been an introduction of new methods of work organization through constructive discussions between employers and their workers' representatives.
Keywords: Impact, COVID-19; pandemic; behavior; social determinants of health; health issues